Dielectric properties of low-temperature sintered forsterite (Mg2SiO4) using high-dispersion and nanoparticle-based solid-state reaction process - Asghar, Ghulam; Dong, Xue; Chae, Sudong; Yoo, Chan Sei; Jeon, Jiho; Woo, Chaeheon; Kim, Tae Yeong; Ahn, Jungyoon; Zhang, Xiaojie; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (Materials Letters, 2023)
Dielectric materials with low dielectric constant and low loss are in high demand due to the rapid development of telecommunication systems toward 5G and 6G. In this work, a modified solid-state reaction method is reported for the synthesis of low dielectric constant forsterite (Mg2SiO4) at low calcination temperatures by using MgO and fumed silica nanoparticles (NPs). The forsterite phase was obtained at 1000 °C, where the sintering temperature was reduced from 1500 °C to 1200 °C. As-synthesized forsterite has a low dielectric constant of 3.9 with low tan δ = 0.00047 at 1 GHz. Low-temperature sintered forsterite is suitable for microelectronics applications.
Keywords: Dielectrics property; Forsterites; High demand; High dispersion; Low dielectric constants; Low temperature sintered; Low-loss; Modified solid state reactions; Solid state reaction method; Solid-state reaction process; Dielectric constant; Forsterite; Mg2SiO4